2007
DOI: 10.1002/jmri.20881
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic MRI for imaging tumor microvasculature: Comparison of susceptibility and relaxivity techniques in pelvic tumors

Abstract: Purpose:To assess the reproducibility of intrinsic relaxivity and both relaxivity-and susceptibility-based dynamic contrast enhanced (DCE) MRI in pelvic tumors; to correlate kinetic parameters obtained and to assess whether acute antivascular effects are seen in response to cisplatin-or taxane-based chemotherapy. Materials and Methods:T 1 -weighted and T 2 *-weighted DCE-MRI and basal R 2 * measurements were performed on three consecutive days in women with gynecological tumors. The third scan was 21.0 (range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
4
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 37 publications
5
28
4
1
Order By: Relevance
“…Contrary to other studies ( 23,28,31 ), we found that the repeatability of K trans in terms of wCV is the same as v e .…”
Section: Roi Analysis Parameterscontrasting
confidence: 99%
“…Contrary to other studies ( 23,28,31 ), we found that the repeatability of K trans in terms of wCV is the same as v e .…”
Section: Roi Analysis Parameterscontrasting
confidence: 99%
“…Previous studies have noted the association between ovarian malignancy and early enhancement following gadolinium injection (13,14), and a recent paper has found that malignant ovarian tumors showed increases in semiquantitative parameters such as enhancement amplitude and maximum slope of enhancement in comparison with benign ovarian tumors (15). Quantitative pharmacokinetic parameters have been calculated from DCE-MRI data at 1.5 T in a variety of pelvic tumors by Lankester et al (30), who assessed the correlations between DCE-MRI and perfusion measurements from a subsequently acquired dynamic susceptibility contrast dataset. The current study builds on the DCE-MRI component of this previous work by assessing metastatic and primary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The current study builds on the DCE-MRI component of this previous work by assessing metastatic and primary tumors. In addition, both spatial coverage and temporal resolution have been improved due to the use of a fast 3D gradient-echo sequence with parallel imaging: this allowed a temporal resolution of 1.6 sec with a coverage of 10 acquired slices, compared with 12 sec and four slices for Lankester et al (30) and 5 sec and three slices for Thomassin-Naggara et al (15), neither of which would be sufficient to accurately characterize uptake at the rate described above. The reductions in signal-to-noise ratio that result from greater speed are offset by the use of a 3D sequence and an increased magnetic field strength of 3 T.…”
Section: Discussionmentioning
confidence: 99%
“…In untreated breast tumors, K trans is dominated by perfusion because of high first pass extraction related to microvessel immaturity. This has been determined in simulations and by empirical observations in xenografts and in human tumors (11,12). This situation changes once vascular shutdown begins to occur with successful therapy when vascular permeability dominates K trans .…”
mentioning
confidence: 99%